Glutathione affinity chromatography for the scalable purification of an oncolytic virus immunotherapy from microcarrier cell culture - Swartz, Andrew R.; Shieh, Yvonne; Gulasarian, Amanda; Curtis, Erik; Hofmann, Carl F.; Baker, Jack B.; Templeton, Neil; Olson, Jessica W. (Frontiers in Bioengineering and Biotechnology, 2023)
Therapeutic viral vectors are an emerging technology with several clinical applications in gene therapy, vaccines, and immunotherapy. Increased demand has required the redevelopment of conventional, low-throughput cell culture and purification manufacturing methods such as static cell stacks and ultracentrifugation. In this work, scalable methods were investigated for the manufacture of an oncolytic virus immunotherapy consisting of a prototype strain of Coxsackievirus A21 (CVA21) produced in adherent MRC-5 cells. Cell culture was established in stirred-tank microcarrier bioreactors, and an efficient affinity chromatography method was developed for the purification of harvested CVA21 through binding of the viral capsids to an immobilized glutathione (GSH) ligand. Bioreactor temperature during infection was investigated to maximize titer, and a decrease in temperature from 37°C to 34°C yielded a 2-3-fold increase in infectivity. After purification of the 34°C harvests, the GSH affinity chromatography elution maintained a >2-fold increase in infectivity and viral genomes but also increased the proportion of empty capsids compared to 37°C harvests. Using material generated from both infection temperature setpoints, chromatographic parameters and mobile phase compositions were studied at lab-scale to maximize infectious particle yields and cell culture impurity clearance. Empty capsids that co-eluted with full capsids from 34°C infection temperature harvests were poorly resolved across the conditions tested, but subsequent polishing anion exchange and cation exchange chromatography steps were developed to clear residual empty capsids and other impurities. Oncolytic CVA21 production was scaled up 75-fold from lab-scale and demonstrated across seven batches in 250 L single-use microcarrier bioreactors and purified with customized, pre-packed, single-use 1.5 L GSH affinity chromatography columns. The large-scale bioreactors controlled at 34°C during infection maintained a 3-fold increase in productivity in the GSH elution, and excellent clearance of host-cell and media impurities was observed across all batches. This study presents a robust method for the manufacture of an oncolytic virus immunotherapy that may be implemented for the scalable production of other viruses and viral vectors which interact with glutathione.